High-speed grinding PROCESS results - Lukovics, Imrich; Bilek, Ondrej (Manufacturing Technology Journal, 2009)
This paper deals with investigation of physical and mechanical characteristics of grinding materials and evaluation shaping of these properties in abrasive tools. Experimental results of high power grinding are introduced. State of stress enumeration of rotating wheels and critical velocity of shaped grinding wheels are shown.
Keywords: Grinding; High-Speed; Simulation; Grinding Grain